Efektifitas Model Pembelajaran CIRC Dalam Meningkatkan Kemampuan Membaca Pemahaman pada Siswa kelas 3 SDN SUKOMANGLI 01 - Bambang Arifianto; Ngatmini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the effectiveness of the Cooperative Integrated Reading and Composition (CIRC) learning model in improving reading comprehension skills of thirdgrade students at SD Negeri Sukomangli 01. The research employed a Classroom Action Research (CAR) method conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The subjects were 14 students. Data were collected through observation, interviews, documentation, and written tests in the form of pretests and posttests. The results showed a significant improvement in students' reading comprehension abilities. In the pretest of Cycle I, all students were in the moderate category (scores 40–59). After the implementation of CIRC in Cycle I, all students improved to the high category (scores 60–80). In Cycle II, 71.43% of students reached the very high category (scores >80), while the rest remained in the high category. The challenges encountered included differences in group member abilities, time limitations, and domination by certain students during group discussions. Nevertheless, the CIRC model proved effective in enhancing both academic performance and collaborative skills. Therefore, the CIRC learning model is recommended as an alternative strategy for teaching Bahasa Indonesia, particularly to improve reading comprehension at the elementary school level. This study aims to examine the effectiveness of the Cooperative Integrated Reading and Composition (CIRC) learning model in improving reading comprehension skills of third-grade students at SD Negeri Sukomangli 01. The research employed a Classroom Action Research (CAR) method conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The subjects were 14 students. Data were collected through observation, interviews, documentation, and written tests in the form of pretests and posttests. The results showed a significant improvement in students' reading comprehension abilities. In the pretest of Cycle I, all students were in the moderate category (scores 40–59). After the implementation of CIRC in Cycle I, all students improved to the high category (scores 60–80). In Cycle II, 71.43% of students reached the very high category (scores >80), while the rest remained in the high category. The challenges encountered included differences in group member abilities, time limitations, and domination by certain students during group discussions. Nevertheless, the CIRC model proved effective in enhancing both academic performance and collaborative skills. Therefore, the CIRC learning model is recommended as an alternative strategy for teaching Bahasa Indonesia, particularly to improve reading comprehension at the elementary school level.